(untitled) (Fiep Bulletin - online, 2013)
This is a descriptive and exploratory study with a quantitative and investigative approach conducted at a public Hospital in Natal/RN. The population consisted of workers from the following sectors: transport of patients (stretcher bearer), nutrition, telephony (PABX), laundry and reception, totaling 36 servers. We had the following objectives: characterize the employees of a hospital in Natal / RN, susceptible to muscle-skeletal discomfort and ergonomic hazards, who agreed to participate in the survey, regarding gender, age and function developed; identify the main muscle-skeletal discomfort developed by these workers and identify the ergonomic hazards that these workers are vulnerable within the work environment. We identified that 75% of staff members were female, aged over 50 years and 36% of those working in the areas of laundry and clothes from the hospital. In relation to muscle-skeletal discomfort senses, we identified that about 70% reported pain, followed by other discomforts such as fatigue, crack, weight, especially in the region of the spine, more specifically in the lumbar, suggesting back pain, being the laundry sector the one that stood out more. As for ergonomic risks, in general, we identify that workers are exposed to: improper posture, long journey, overhead labor, inadequate and deficient equipment and furnishings, monotony and repetitiveness. We conclude that a change is needed in organizing the work of this institution, aimed at prevention and health promotion of workers, emphasizing the importance of the implementation of Ergonomics in the planning and organization of work in hospital environments.